ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI DAN SISTEM PENGENDALIAN INTERNAL DALAM MENCEGAH FRAUD PADA BUMDESMA SENDANG - Farika, Nila Chusna; Ni’am, Zaki Bahrun (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
The growing times the higher the fraudulent or common levels in the Fraud. Fraudis a criminal fraud that aims to benefit financially. ACFE mentions there are threetypes of Fraud that is Asset Misoppropration, Fraud of financial statements andcorruption. The greatest impact of Fraud is poverty, so the government forms aempowerment program called PNPM-MPd that eventually transforms intoBumdesma or a village-owned business entity. BUMDESMA Sendang is far fromthe city center, where the majority of local human resources are lacking ineducation. But this situation does not make Bumdesma Sendang suffered cheating.Because Bumdesma Sendang is able to implement accounting information systemsand internal control systems in preventing fraud well. This research uses descriptivequalitative approach. Based on findings by researchers, the recording system inBumdesma Sendang still using Microsoft Excel and manual recording, no specialapp to record it. Internal controls on Bumdesma Sendang on essence are done in thebasis (supervisory attached) by BP or the Supervisory Agency. But everyoneinvolved in it has the right to oversee each other. The accounting system of theinternal information and the internal control system is well but not maximized so itis still vulnerable to the fraud or fraud. To the foreheads expect more maximal withmore systems and controls that are more maximal so that the occurrence of fraudsmaller.Keywords: Accounting Information Systems, Fraud And Internal Control Systems